DESAIN DAN KARAKTERISASI SEL SURYA SISTEM ELEKTRODA TEMBAGA (I) OKSIDA (Cu2O/Al) MODEL PIPA PADA LARUTAN NATRIUM SULFAT (Na2SO4) - Rahma yulis lubis; Siltiwi Mandar; Rahadian Zainul (Jurnal Periodic Jurusan Kimia UNP, 2019)
Research has been conducted on "Design and Characterization of Solar Cells for Copper Oxide Electrode System (Cu2O) Model Pipes in Sodium Sulfate Solution (Na2SO4)". Solar cells (photovoltaic cells) are devices that have the ability to convert sunlight energy into electrical energy by applying the principle of photovoltaic. The principle of photovoltaic is defined as a phenomenon of the emergence of electrical voltage due to the contact of two electrodes connected to a solid or liquid system when exposed under sunlight. This study aims to determine the effect of sodium sulfate electolite solution concentration, the effect of measurement time on the generated current, determination of the concentration of solar cells, and the effect of design on electric current. In this solar cell study, the optimum concentration of sodium sulfate was 0.75 M. The measurement time produced power was at 12.00 WIB, then the stability of solar cells on the fifth day and the optimum design of solar cells was in the design 2. The maximum power obtained is 0.12325 mWatt and the electrode ability to produce electricity per area is 49.938412 mWatt / m2 with. The electrode area used is 0.00246804 m2.